2020 21st IEEE International Conference on Mobile Data Management (MDM) 2020
DOI: 10.1109/mdm48529.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic macro scale traffic flow optimisation using crowd-sourced urban movement data

Abstract: How can urban movement data be exploited in order to improve the flow of traffic within a city? Movement data provides valuable information about routes and specific roads that people are likely to drive on. This allows us to pinpoint roads that occur in many routes and are thus sensitive to congestion. Redistributing some of the traffic to avoid unnecessary use of these roads could be a key factor in improving traffic flow.Many proposed approaches to combat congestion are either static or do not incorporate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Table 2 lists industrial applications in maritime industries [262,82], transportation [2,13,10,171,199,16], autonomous vehicles [263,228], health [2,178,10], behavior analysis [199,16], manufacturing [216,10,77] and indoor positioning [216,2].…”
Section: Industrial Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 lists industrial applications in maritime industries [262,82], transportation [2,13,10,171,199,16], autonomous vehicles [263,228], health [2,178,10], behavior analysis [199,16], manufacturing [216,10,77] and indoor positioning [216,2].…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…The results show that the response surface methods (particularly constrained optimization using response surfaces) have consistently good performance under all scenarios. 4.1 Industrial Applications Later on Arp et al [13] worked on the problem of determining best alternative routes in case of congestion or diversions using movement data. They use parametric optimization and network based real-time forecasting for traffic flow en route on a network.…”
Section: Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these approaches have considered studying the network properties of LBSN data without considering how such information can be used in improving urban aspects. Recently, Arp et al [2] have shown how such data can be used in optimising the state of traffic within the city. A recent trend in which private companies make their data available through various "Data for Good" programs helps to advance research in the field.…”
Section: Related Workmentioning
confidence: 99%